Acesso a medicamentos em população assistida por diferentes modelos de atenção básica nas regiões sul e nordeste do Brasil - Paniz, Vera Maria Vieira (2009)
This study aimed to evaluate the prevalence of access to continuous-use medicines for treatment of systemic arterial hypertension, diabetes mellitus, and/or mental health problems, and the associated factors. A cross-sectional study was developed under the Project for the Expansion and Consolidation of the Family Health Program in 41 cities in South and Northeast Brazil. The sample included 4,060 adults and 4,003 elderly living in the coverage areas for primary health care clinics. Prevalence of access to continuous-use medicines was 81% in non-elderly adults and 87% in the elderly. Greater access was associated with the following factors: adults in South Brazil older age, higher socioeconomic status, type of chronic disease, and participation in support groups in the primary health clinic area; adults in the Northeast systemic arterial hypertension with or without diabetes mellitus; elderly in the South more schooling; and elderly in the Northeast older age, more schooling, non-smoking, enrolment in the primary health care clinic coverage area, and the family health care model. The results show important inequity in health, reinforcing the need for policies to expand access, mainly for lower-income population groups.